“The Socio-Political Significance of Artificial Intelligence Technologies in the Process of Forming a Civil Society” (Eurasian Journal of Humanities and Social Sciences, 2025)
This article analyzes the importance of artificial intelligence technologies in the process of forming a strong civil society. It highlights the opportunities for increasing citizens’ sociopolitical activity under conditions of digital transformation. Based on international experience and Uzbekistan’s practical context, the influence of artificial intelligence on the functioning of civil society institutions is recognized. The article also presents proposals to strengthen the integration of civil society and digital governance, and to introduce the “Digital Public Oversight Platform”.